2020
DOI: 10.1124/jpet.120.000063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Stressed Transgenic Mice Overexpressing H2-Histamine Receptors in the Heart

Abstract: We studied transgenic mice with cardiac-specific overexpression of H 2 -histamine receptors (H 2 -TG) by using the a-myosin heavy-chain promoter. We wanted to address whether this overexpression would protect the heart against paradigmatic stressors. To this end, we studied isolated atrial preparations in an organ bath under normoxic and hypoxic conditions and after prolonged exposure to high histamine concentrations. Moreover, we assessed cardiac function using echocardiography in mice with cardiac hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 41 publications
4
32
1
Order By: Relevance
“…In addition, studies have found increased ANP levels in mice with acute regional cardiac ischemia [ 57 ]. The overexpression of receptors that stimulate cAMP generation, such as H 2 receptors [ 58 ] or A 2A -adenosine receptors [ 35 ], can protect isolated left atria against acute hypoxia in the same experimental setup. Other studies have reported that cardiac ischemia in mice hearts causes increased IL-6 [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found increased ANP levels in mice with acute regional cardiac ischemia [ 57 ]. The overexpression of receptors that stimulate cAMP generation, such as H 2 receptors [ 58 ] or A 2A -adenosine receptors [ 35 ], can protect isolated left atria against acute hypoxia in the same experimental setup. Other studies have reported that cardiac ischemia in mice hearts causes increased IL-6 [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals were maintained and handled according to approved protocols of the animal welfare committees of the Martin Luther University of Halle-Wittenberg, Germany. The generation and initial characterization of mice with cardiac-specific overexpression have been reported from our group (Gergs et al 2019(Gergs et al , 2020Neumann et al 2021b). We used an α-myosin heavy chain promoter to overexpress the human H 2 -histamine receptor in the mouse heart and tested the offspring for transgenes using the polymerase chain reaction (Gergs et al 2019(Gergs et al , 2020Neumann et al 2021b).…”
Section: Transgenic Micementioning
confidence: 99%
“…Drugs like Famotidine (tradename; Pepcid) are histamine receptor antagonists that are routinely used to treat, and prevent certain types ulcers, and to treat conditions that cause the stomach to produce too much acid, and also to treat gastroesophageal reflux disease condition. Clinical evidence of the role of histamine in heart has been well documented, and histamine receptor antagonist in hypertension are cardioprotective [15][16][17]. Interestingly, HCQ is unique in the sense that, at low doses, it mitigates or blunts both the virus's direct effects, as well as the immune reaction/response.…”
Section: Introductionmentioning
confidence: 99%